Implementasi Pendidikan Kewarganegaraan Dalam Mewujudkan Identitas dan Integrasi Nasional - Akma Khairun Nisa; Lona Mardiati; Sasmi Nelwati (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to find out that through the implementation of citizenship education, this nation can realize a national identity and integrity. Citizenship education plays a role in preparing young people from an early age to become citizens who have good knowledge and noble character, and have skills that are devoted to the nation and state. Citizenship education has a role in introducing national identity and national integrity. National identity is the characteristic of a nation so that there are differences between each nation and country. National integration is defined as the unification or blending of a nation so that it becomes a unified whole. In this research, the basis of education will be related to and realizing a national identity and integrity in citizenship through qualitative methods or literature review.